2019
DOI: 10.1093/rb/rbz006
|View full text |Cite
|
Sign up to set email alerts
|

Fibroadhesive scarring of grafted collagen scaffolds interferes with implant–host neural tissue integration and bridging in experimental spinal cord injury

Abstract: Severe traumatic spinal cord injury (SCI) results in a devastating and permanent loss of function, and is currently an incurable condition. It is generally accepted that future intervention strategies will require combinational approaches, including bioengineered scaffolds, to support axon growth across tissue scarring and cystic cavitation. Previously, we demonstrated that implantation of a microporous type-I collagen scaffold into an experimental model of SCI was capable of supporting functional recovery in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(71 reference statements)
3
15
0
Order By: Relevance
“…One day after SCI, the bilateral hind limbs of all SCI rats were paralyzed, while the bilateral hind limbs of Sham group were normal. Both behavioral assessment and electrophysiological studies demonstrated that the 3D-CC-BDNF group showed better locomotor function recovery compared with the 3D-CC+BDNF group ( Figs 3A–G and 4A–E ). Compared to implanting 3D-CC+BDNF or without implanting scaffolds, implanting 3D-CC-BDNF could significantly increase the BBB scores of right and left hindlimbs from 2 to 8 weeks after surgery ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…One day after SCI, the bilateral hind limbs of all SCI rats were paralyzed, while the bilateral hind limbs of Sham group were normal. Both behavioral assessment and electrophysiological studies demonstrated that the 3D-CC-BDNF group showed better locomotor function recovery compared with the 3D-CC+BDNF group ( Figs 3A–G and 4A–E ). Compared to implanting 3D-CC+BDNF or without implanting scaffolds, implanting 3D-CC-BDNF could significantly increase the BBB scores of right and left hindlimbs from 2 to 8 weeks after surgery ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Although a number of laboratories have focused on the implantation of orientated, micro-porous collagen scaffolds in an attempt to bridge complete or partial experimental spinal cord lesions, only a limited degree of functional recovery has been observed, and even this could not be correlated with axonal regeneration through the implants [ 21 , 22 , 47 , 48 , 49 ]. Leptomeningeal fibroblasts were assumed to be responsible for preventing axonal re-growth [ 21 , 22 ], and even our own morphometric immunohistochemical studies supported the fibroblast-like nature of these scarring cells [ 32 , 33 ]. By 10 weeks after scaffold implantation into the adult rat cervical spinal cord, only limited penetration by host neuronal and glial elements could be demonstrated.…”
Section: Discussionmentioning
confidence: 86%
“…Although limited functional recovery has been observed over a period of 10 weeks following implantation of a longitudinally microstructured collagen scaffold in an in vivo model of SCI, this was likely due to some degree of tissue sparing and reduced cystic cavitation rather than any axon regeneration through the scaffold, since there was a lack of any substantial host neural tissue integration with the implant [ 30 ], a situation that could not be significantly improved by co-implanting purified populations of axon growth-promoting olfactory ensheathing cells [ 31 ]. Our more recent immunohistochemical studies of such long-term lesion/implantation sites have demonstrated sheets of fibroblast-like scarring cells of uncertain identity forming an intense zonula occludens-1 (ZO-1) immunoreactive transition zone between the collagen implant and the surrounding host tissues [ 32 , 33 ]. The general lack of suitable quality immunohistochemical markers for specific labelling of fibroblast sub-types has prompted us to test the hypothesis that a clearer understanding of the type and origin of the cells in the transition zone could be obtained by investigating their fine structural features by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been demonstrated that macrophages are responsible for fibroblast recruitment to the injury site and depletion of hematogenous macrophages results in reduced fibroblast density and basal lamina formation in the lesion site, and this is associated with increased axonal growth [80]. Furthermore, the proliferation of fibroblasts can induce fibrosis around biomaterial implants [81][82][83] a particular caveat of biomaterial use [84], and have been implicated in the relatively poor implant-host integration in some implanted scaffolds [65,85].…”
Section: Fibroglial Scar Formationmentioning
confidence: 99%